G127(P) Apnea and Thrombocytopenia as important markers for fungal sepsis in the Neonatal Unit and the role of selective fluconazole prophylxis. (7th April 2014) - Mukhopadhyay, D; Das, M; Chaudhuri, J; Sabui, T; Chakraborty, S; Chatterjee, S; Banerjee, T
Abstract : Aims: Neonatal fungal septicaemia is clinically indistinguishable from any other form of septicaemia and has high mortality and morbidity. This study aims at evaluating the associated risk factors in fungal sepsis in the neonates and the effect of selective fluconazole prophylaxis. Methods: In the first phase, the sick neonates admitted over a period of eight months were investigated for risk factors and data analysed. In the subsequent four months, fluconazole prophylaxis was administered to the admitted newborns with at least two risk factors identified in the first phase of the study. Major congenital anomalies, admission for <48hrs, altered liver function tests and exchange transfusion were exclusion criteria. Analyses was done using Graphpad Instat software version 3.10, 32 bit for Windows created July 2009. Results: Invasive procedures were significantly high in babies with fungal sepsis, but there was no significant difference when compared to those with bacterial sepsis. Conclusion: In addition to prematurity, ELBW and VLBW, other risk factors associated with invasive candidiasis are antibiotics for > 10 days, thrombocytopenia and apnea (beyond first seven days of life) for both term and preterm neonates. Implementation of fluconazole prophylaxis in sick babies based on any two of the above risk factors significantly reduces the incidence of fungal septicemia without the emergence of fluconazole resistant strains. Mortality is significantly higher in cases of fungal sepsis than in cases of bacterial sepsis.